Comparative evaluation of surface roughness of herbal denture cleansing tablet containing essential oils of tulsi and lemongrass, 0.12% chlorhexidine digluconate, and commercially available denture cleansing tablet on heat cure polymethyl methacrylate denture base resin: An in vitro study - Harpreet Singh Manaktala; Raghunath Patil (Indian Journal of Health Sciences and Biomedical Research KLEU, 2023)
Context: Poor denture hygiene is a risk factor for oral infections and systemic dissemination. Denture cleanliness is essential to prevent malodor, poor esthetics, and the accumulation of plaque/calculus with its deleterious effect on the mucosa. Denture base resins become colonized by several microbial species in the oral cavity. There are number of tablets, pastes, and powders available for cleaning dentures with a variety of manufacturer's claims for their relative efficacies. The increase in the use of denture cleaners can lead to more wear of the heat cure polymethyl surface leading to surface roughness. The increase in the surface roughness of the heat cure polymethyl methacrylate can lead to increase in denture biofilm. Candida species yeasts are the most common species associated with denture biofilm. AIM: To evaluate and compare the surface roughness of herbal denture cleansing tablet, commercially available denture cleansing tablet and 0.12% chorhexidine digluconate on heat cure polymethyl methacrylate denture base resin. MATERIALS AND METHODS: 84 acrylic blocks were fabricated of heat cure polymethyl methacrylate resin and were divided into four groups of 21 samples each, which were disinfected using Phytopharmaceutical denture cleansing tablet containing Tulsi and Lemongrass, fittydent denture cleansing tablets, chlorhexidine, and water which acted as control. Surface roughness evaluation was done before and after disinfection of the heat cure polymethyl methacrylate blocks. RESULTS: The results showed that highest surface roughness was seen with fittydent commercially available denture cleansing tablet followed by chlorhexidine group and least surface roughness was seen with phytopharmaceutical denture cleansing tablet. CONCLUSION: Phytopharmaceutical denture cleansing agent containing tulsi and lemongrass can be recommended as a denture cleansing agent for complete dentures over chlorhexidine and commercially available denture cleansing tablets.